Structural Transitions in MgSiO3 Glasses and Melts at the Core‐Mantle Boundary Observed via Inelastic X‐ray Scattering. Issue 23 (6th December 2019) - Kim, Yong‐Hyun; Yi, Yoo Soo; Kim, Hyo‐Im; Chow, Paul; Xiao, Yuming; Shen, Guoyin; Lee, Sung Keun
Abstract: The structural adaptation in MgSiO3 melts under compression up to 130 GPa is the key to revealing the origins of the pronounced negative buoyancy of the melts at the core‐mantle boundary (CMB). A full understanding of the melt densification requires study of the pressure‐induced changes in the bonding configuration around oxygen at the CMB, which has proven to be difficult to measure. Here, the experimental breakthrough in O K ‐edge inelastic X‐ray scattering enables collection of the spectra of MgSiO3 glasses up to 130 GPa, along with ab initio molecular dynamics simulations, revealing the electronic bonding transitions around heavily compressed oxygen. The spectral results indicate the emergence of denser network structures around oxygen, stemming from contractions in the Mg‐O and O‐O distances associated with flexible topological and short‐range rearrangements around Si. The results unveil the electronic structure and thus the nature of densification in dense partial melts at the CMB. Plain Language Summary: A thin ultralow velocity zone at the bottom of mantle is characterized by reduced seismic wave velocities and enhanced density, suggesting the possible presence of molten silicates at a depth of 2, 850 km ( 130 GPa of pressure). How the melts densify near the core‐mantle boundary is unclear. Because oxygen occupies the major volume fraction of silicates, the melt densification is dominated by the reorganization of oxygen during compression. However, the oxygen bonding environments in MgSiO3 melt—a model mantle melt—near the core‐mantle boundary are unknown. Here, the inelastic X‐ray scattering spectra of MgSiO3 glasses and liquids up to 130 GPa revealed the electronic bonding transitions around compressed oxygen that are not observed at low pressures and substantially differ from those in the crystalline MgSiO3 bridgmanite. The spectral results indicate the pressure‐induced emergence of denser network structures around oxygen, stemming from gradual contractions in the Mg‐O and O‐O distances associated with flexible topological and short‐range rearrangements around Si. The densification around oxygen near megabar pressures potentially contributes to the gravitational stabilization of the complex partial melts in the deeper part of the mantle toward ultralow velocity zone. Key Points: The O K ‐edge inelastic X‐ray scattering spectra of MgSiO3 glass up to 130 GPa revealed the bonding transitions around oxygen at CMB The emergence of dense oxygen networks near megabar pressure stems from contractions in the Mg‐O and O‐O distances, unique to MgSiO3 melts The results provide insights into densification mechanism of dense partial melts anticipated to comprise the ULVZ at the CMB